Comparison of Catalysts Preyssler and Silica-Supported Nano Preyssler in the Synthesis of Acetyl Salicylic Acid. Issue 1 (2012) - Nazari, H.; Ahmadpour, A.; Bamoharram, F. F.; Heravi, M. M.; Eslami, N.
Abstract : The extensive demand for cleaner environment is forcing chemical industry to use less hazardous materials. In this regard, heteropolyacids attracted considerable amount of interest due to the less toxic behavior in addition of possessing higher acidity. Heteropoly acids have been used as catalysts for the reaction of salicylic acid with acetic anhydride. The performance of different forms of heteropoly acids in the presence of acetic anhydride as acetylating agent for acetylation of salicylic acid was compared. The best conditions were observed using Preyssler and Silica-supported Preyssler Nanoparticles as catalysts. The catalyst is recyclable and reusable.